Osong, Value Transformation of Oral Tradition in Regional Language Learning of SMPN 1 Bulupoddo, Sinjai Regency - Hardianti Hasyim; Ery Iswary; Ilham Ilham; Firman Saleh (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2021)
This study is a quantitative descriptive study that describes the ability to read blanks of eighth-grade students of SMPN 1 Bulupoddo, Sinjai Regency. Based on the presentation of the results of the data analysis above, it can be described in detail about the osong reading ability of the eighth-grade students of SMPN 1 Bulupoddo, Sinjai Regency. Students' test results in reading blanks are then analyzed based on predetermined criteria or assessment indicators, namely the pronunciation aspect with a score of 1 to 1, intonation aspect with a score of 1 to 3, gesture aspect with a score of 1 to 3, expression aspect with a score of 1 up to 3, the aspect of appreciation with a score of 1 to 3, the aspect of appearance with a score of 1 to 3. Of the six aspects of the assessment of reading blanks, the maximum score is 18. In the contents of elong osong itself, the theme contained in it is the figure of a Bugis human who is brave and does not stand still and becomes a coward towards the nation and homeland. The tones used are generally satirical and patronizing. The atmosphere or state of the reader's soul after reading or listening to the osong can be a booster or an incendiary. While the results of the current study emphasize the ability of students to read blanks. This is what distinguishes previous research from the results of the present study. Keywords: Osong, Value Transformation, Learning, Regional Language, Sinjai